Implementation of a fetal ultrasound telemedicine service: women's views and family costs - V. J. Smith; A. Marshall; M.L.S Lie; E. Bidmead; B. Beckwith; E. Van Oudgaarden; S. C. Robson (BMC, 2021)
Abstract Background The complexity of fetal medicine (FM) referrals that can be managed within obstetric units is dependent on the availability of specialist ultrasound expertise. Telemedicine can effectively transfer real-time ultrasound images via video-conferencing. We report the successful introduction of a fetal ultrasound telemedicine service linking a specialist fetal medicine (FM) centre and a remote obstetric unit. Methods Over a four-year period from October 2015, all women referred for FM consultation from the obstetric unit were seen via telemedicine, excluding cases where invasive testing, intrauterine therapy or cardiac anomalies were anticipated. The outcomes measured included the indication for FM referral; scan duration and image and sound quality during the consultation. Women's perceptions of the telemedicine consultation and estimated costs to attend the FM centre were measured by a structured questionnaire completed following the first telemedicine appointment during the Phase 1 of the project. Results Overall, 297 women had a telemedicine consultation during Phase 1 (pilot and evaluation) and Phase 2 (embedding and adoption) of the project, which covered a 4 year period 34 women completed questionnaires during the Phase 1 of the study. Travel to the telemedicine consultation took a median (range) time of 20 min (4150), in comparison to an estimated journey of 230 min (120,450) to the FM centre. On average, women would have spent approximately £28 to travel to the FM centre per visit. The overall costs for the woman and her partner/ friend to attend the FM centre was estimated to be £439. Women were generally satisfied with the service and valued the opportunity to have a FM consultation locally. Conclusions We have demonstrated that a fetal ultrasound telemedicine service can be successfully introduced to provide FM ultrasound of sufficient quality to allow fetal diagnosis and specialist consultation with parents. Furthermore, the service is acceptable to parents, has shown a reduction in family costs and journey times.